2020
DOI: 10.1109/access.2020.2992660
|View full text |Cite
|
Sign up to set email alerts
|

NOMA in Cooperative Underlay Cognitive Radio Networks Under Imperfect SIC

Abstract: In conventional cognitive radio (CR), the users in secondary network (SN) can only access the idle spectrum when users in primary network (PN) are absent. This novel strategy provides higher spectrum efficiency when detecting the presence of the PN. Hence, spectrum utilization of the traditional scheme can be further improved as exploiting application of non-orthogonal multiple access (NOMA). As combination of CR and NOMA, such CR-NOMA has been proposed to improve spectrum efficiency to adapt to requirements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 41 publications
1
55
0
Order By: Relevance
“…In parallel, non-orthogonal multiple access (NOMA) techniques have received considerable research interest due to their ability to improve the spectral efficiency of wireless networks [ 8 ]. For instance, using NOMA can be combined with cognitive radio to increase spectrum efficiency [ 9 ]. Although the applications of NOMA in HSTRNs have not been explored extensively, significant performance improvements can be achieved with NOMA-enabled HSTRNs.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, non-orthogonal multiple access (NOMA) techniques have received considerable research interest due to their ability to improve the spectral efficiency of wireless networks [ 8 ]. For instance, using NOMA can be combined with cognitive radio to increase spectrum efficiency [ 9 ]. Although the applications of NOMA in HSTRNs have not been explored extensively, significant performance improvements can be achieved with NOMA-enabled HSTRNs.…”
Section: Introductionmentioning
confidence: 99%
“…To address some of the 5G challenges including spectrum efficiency and massive connectivity, it is necessary to study the combination of NOMA with CR networks while maintaining reliable transmission of primary and secondary users. In various circumstances of the underlay CR-NOMA developed in [7][8][9][10], a superimposed signal is sent by the secondary transmitter to the secondary NOMA destination users. The authors concluded that if the PA factors and target rates are accurately chosen, the performance of NOMA users can be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…1, there exist four data streams in each round of transmission, i.e., two downlink data streams from the BS to the two users via the RS, and two uplink data streams from the two users to the BS via the RS. Existing schemes, such as those in [23] [24], requires at least four time slots to complete each round of transmission due to the half-duplex mode of the relay.…”
Section: Introductionmentioning
confidence: 99%